The diagnostic assessment of inherited platelet function defects: part 1: an overview of the diagnostic approach and laboratory methods - Hoepner, Gero Martin; Althaus, Karina; Müller, Jens; Zieger, Barbara; Pavlova, Anna; Boeckelmann, Doris; Knöfler, Ralf; Bugert, Peter; Kehrel, Beate; Streif, Werner; Birschmann, Ingvild; Rühl, Heiko; et al. (Hämostaseologie, 2025)
In this article, our goal is to offer an introduction and overview of the diagnostic approach to inherited platelet function defects (iPFDs) for clinicians and laboratory personnel who are beginning to engage in the field. We describe the most commonly used laboratory methods and propose a diagnostic four-step approach, wherein each stage requires a higher level of expertise and more specialized methods. It should be noted that our proposed approach differs from the ISTH Guidance on this topic in some points. The first step in the diagnostic approach of iPFD should be a thorough medical history and clinical examination. We strongly advocate for the use of a validated bleeding score like the ISTH-BAT (International Society on Thrombosis and Haemostasis Bleeding Assessment Tool). External factors like diet and medication have to be considered. The second step should rule out plasmatic bleeding disorders and von Willebrand disease. Once this has been accomplished, the third step consists of a thorough platelet investigation of platelet phenotype and function. Established methods consist of blood smear analysis by light microscopy, light transmission aggregometry, and flow cytometry. Additional techniques such as lumiaggregometry, immune fluorescence microscopy, and platelet-dependent thrombin generation help confirm and specify the diagnosis of iPFD. In the fourth and last step, genetic testing can confirm a diagnosis, reveal novel mutations, and allow to compare unclear genetics with lab results. If diagnosis cannot be established through this process, experimental methods such as electron microscopy can give insight into the underlying disease.